PENERAPAN ARSITEKTUR KONTEMPORER PADA BANGUNAN ART CENTER AND GALLERY DI KOTA MEDAN - Darma, Septia; Barky, Neneng Yulia (Universitas Medan Area, 2024)
North Sumatra is one of the largest islands in Indonesia with the capital city in Medan. It has an area of 72,460.744 km2, with a population of 2,494,512 people, and is surrounded by 21 districts. known as the paris of Sumatra van, which has a lot of interesting cultural diversity. It can be seen from several aspects of people's lives, ranging from grammar, customs, clothing, food, and art. Medan City itself has quite recognizable arts including Malayu art, and Batak art. According to Perda (Regional Regulation of Medan City on the Preservation of Cultural Heritage Buildings and Environments), emphasizing that economic development in Medan City must prioritize competitive advantages, through infrastructure development and preservation of regional culture, especially in the field of arts. Therefore the city of Medan needs a place or place of art, to accommodate art activities, one of which is this Art Center and Gallery, which will be built with the concept of contemporary architecture by utilizing aspects of the environment, both in terms of materials, spaces, building forms or circulation. As well as applying the characteristics and design principles of contemporary architecture as a solution in designing art centers and gallery in the city of Medan.